Intravenous Dexmedetomidine for the Treatment of Shivering During Cesarean Delivery Under Neuraxial Anesthesia: A Randomized-controlled Trial. Issue 2 (June 2020) - Lamontagne, C.; Lesage, S.; Villeneuve, E.; Lidzborski, E.; Derstenfeld, A.; Crochetieìe, C.
Abstract : ( Can J Anesth / J Can Anesth . 2019;66:762–771) Neuraxial anesthesia is preferable for cesarean deliveries (CDs), as it allows mothers to be awake and avoids the associated risks of general anesthesia. However, an estimated 53% of patients under neuraxial anesthesia suffer from shivering. Uncontrolled shivering intervenes with vital sign monitoring, causes physiological stress, and affects a patient's satisfaction and comfort. The most common pharmacological treatment for shivering is meperidine (a synthetic opioid). However, as this drug becomes increasingly scarce in North American hospitals, an effective alternative agent is desired. Dexmedetomidine is an alternative treatment for shivering and can alleviate shivering while avoiding side effects associated with opioids. The aim of this study was to test whether a single bolus of 30 μg intravenous (IV) dexmedetomidine, administered 5 minutes after childbirth, could reduce shivering during CD under neuraxial anesthesia.